Potential psychosocial impact of COVID-19 on children: a scoping review of pandemics and epidemics - Kaitlyn A Merrill; Trevyna NN William; Kayla M Joyce; Leslie E Roos; Jennifer L Protudjer (Inishmore Laser Scientific Publishing Ltd, 2021)
# Background Physical distancing and health measures, such as school closures and work-at-home mandates, implemented to mitigate the transmission of COVID-19, will likely have far-reaching impacts on children's psychosocial health and well-being. We aimed to examine extant literature on pandemics and epidemics to draw comparisons regarding COVID-19 on children's psychosocial health and secondary outcomes, including nutritional, financial and child safety outcomes. # Methods Articles were searched within the Medline, Global Health, PsycINFO, and CINAHL databases on 11 June 2020. Grey literature was also examined from the World Health Organization (WHO) and United Nations Children's Fund (UNICEF) until 24 July 2020. # Results A total of 8,332 articles were screened for eligibility by two independent reviewers. Of these, 7,919 and 413 articles were from academic databases and additional sources, respectively. Results on child outcomes were extracted and collated. Seventy-three articles met inclusion criteria. Children have faced significant challenges with 12% of articles indicating loneliness/depression, 19% anxiety, 7% grief, 10% stress-related disorders, 25% child abuse, 8% family conflict, and 12% stigma during pandemics/epidemics. Furthermore, 25% of articles indicated economic challenges, 23% negative academic impacts, 33% improper nutrition, and 21% reduced opportunities for play/increased screen time. These challenges were exacerbated among children who were female, have a disability, or who were a migrant/displaced child. # Conclusions Pandemics and epidemics have had diverse and widespread negative consequences for children. Findings can inform the development and implementation of resources during the COVID-19 pandemic to protect child health and well-being.